Evaluation of Physico-Chemical Characteristics of Soil Samples Collected from Harrapa-Sahiwal (Pakistan) - IMRAN, MUHAMMAD; KHAN, AMIN-UL-HAQ; KANWAL, FARAH; LIVIU, MITU; AMIR, MUHAMMAD; ADNAN IQBAL, MUHAMMAD (Asian Journal of Chemistry, 2010)
The soil of different sites of the Harappa museum situated at Sahiwal district was collected and investigated for pH, electrical conductivity, organic matter, micronutrients and macronutrients. The soil is saline sodic. pH was found to be in the range of 7.62-8.27 which is slightly neutral to basic. Electrical conductivity was in the range 8.9-12.0 mS/ cm while percentage of organic matter was 0.276-1.035. The elements like Na, K, Ca, Mg, Zn, Ni, Cu, Mn, Mo, Se, B, P, N, S, Cl were found in the range, Na (1035-9050 mg/kg), K (3050-6000 mg/kg), Ca (153- 260 mg/kg), Mg (259-689 mg/kg), Zn (31-85 mg/kg), Ni (7.3-17.8 mg/ kg), Cu (70-91 mg/kg), Mn (3.1-20.3 mg/kg), Mo (16.1-24.4 mg/kg), Se (0.01-0.062 mg/kg), B (6.7-16.6 mg/kg), P (164-696 mg/kg), N (5.76- 13.38 mg/kg), S (62-281.3 mg/kg), Cl (102.3-200 mg/kg), respectively. The overall contents of the above parameters were found to be above permissible limits. The main purpose of the study is to report physicochemical composition of soil of archaeological interest and to provide guidelines for the restoration and rehabilitation of vegetation.